2018
DOI: 10.35911/torani.v1i2.4440
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Addition Papain Enzyme in Artificial Diet on the Metamorphosis Rate and Glycogen Content of Mangrove Crab Larvae (Scylla olivacea)

Abstract: In the rearing of fish larvae, artificial feed can be given when digestive enzymes have been produced. To improve the ability of fish larvae to utilize artificial feeds can be done with the addition of exogenous enzyme into the artificial feeds. The aim of this study was to determine the dose of papain enzyme and the correct predigest artificial feeding stadium on metamorphosis rate and glycogen content of mangrove larvae (Scylla olivacea). The experimental design used was a factorial pattern with a complete r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…The lowest of total amino acid content was also at a dose of enzyme papain 0.0%, i.e. only 29.92%, whereas, at a dose of papain enzyme 1.5%, 3.0% and 4.5% were 36.47%, 37.26%, and 36.04% respectively [11]. The results of Kurniawan et al [17] also showed the same pattern, the amino acid content of the squid ink sample without the addition of papain enzyme was also lower than the amino acid content of the hydrolysed sample with the addition of 2%.…”
Section: B Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The lowest of total amino acid content was also at a dose of enzyme papain 0.0%, i.e. only 29.92%, whereas, at a dose of papain enzyme 1.5%, 3.0% and 4.5% were 36.47%, 37.26%, and 36.04% respectively [11]. The results of Kurniawan et al [17] also showed the same pattern, the amino acid content of the squid ink sample without the addition of papain enzyme was also lower than the amino acid content of the hydrolysed sample with the addition of 2%.…”
Section: B Discussionmentioning
confidence: 88%
“…The result of analysis soluble protein content and protein hydrolysis levels showed that in the artificial diet which hydrolysis with enzyme papain 0% and 1,5% significant different but was lowest and insignificantly different compared to a dose of enzyme papain 3.0% and 4,5%. The content of soluble protein at a dose of enzyme papain of 3.0% and 4.5% was not different [11]. The low content of dissolved protein at the dose of papain enzyme was thought to be due to the limited concentration of enzymes that cannot hydrolyse the protein well…”
Section: B Discussionmentioning
confidence: 90%
See 3 more Smart Citations